Analisis Faktor-Faktor Kualitas Tidur Pada Remaja Menurut Teori Sosial Kognitif (SCT) Tahun 2020-2025 - Nabila Fitri Ramadhani (Barongko: Jurnal Ilmu Kesehatan, 2026)
Sleep quality is one of the important factors that play a role in the physical, mental, and cognitive development of adolescents. However, various changes in lifestyle and environment have caused more and more adolescents to experience sleep quality disorders. This study aims to analyze the factors that affect sleep quality in adolescents based on the Social Cognitive Theory (SCT) approach by reviewing relevant scientific literature. The method used was a literature review of national and international articles published between 2020 and 2025. The literature search was conducted using the Google Scholar and PubMed databases, and 10 articles that met the inclusion criteria were obtained. The results of the study show that individual factors are the most dominant factors affecting adolescent sleep quality, including stress levels, excessive use of gadgets (social media and online games), pre-sleep habits, and the use of sleeping pills and caffeine. Environmental factors, such as noise, lighting, and room temperature, also play a role, although they have not been extensively studied. Poor sleep quality has an impact on decreased concentration in learning, mental health disorders such as anxiety and depression, and decreased physical fitness. In conclusion, adolescent sleep quality is influenced by the interaction between individual and environmental factors as described in social cognitive theory. Promotive and preventive efforts are needed through the habit of healthy sleep behavior and supportive environments to improve adolescent sleep quality.